Gamma Irradiation Treatment of Bactrocera dorsalis Hendel (Diptera: Tephritidae) in Snake Fruit - Novi Kusumaning Astuti; Suputa Suputa; Nugroho Susetyo Putra; Murni Indarwatmi (Jurnal Perlindungan Tanaman Indonesia, 2019)
Snake fruit (Salacca zalacca) is a unique fruit and it has decadent prospects to be developed as an export commodity. Nevertheless, oriental fruit fly, Bactrocera dorsalis Hendel seems to decrease the quantity and quality of this fruit. On the other side, irradiation has been developed as a standard quarantine treatment to disinfest fruit fly on fruit. The objective of this research was to determine impact of irradiation by Cobalt-60 gamma-ray on the development and survivorship of eggs and the third instar of fruitfly larvae using in-vitro and in-vivo approaches and minimum dose of Cobalt-60 gamma rays applied for snake fruit. Six doses of gamma-ray, i.e. 0 (control), 25, 50, 75, 100, 125 and 150 Gy were used in this experiment. The results showed that Cobalt-60 disturbed development and survivor rate of B. dorsalis. The development of eggs into pupa was failed when treated with Cobalt-60 at any doses, while the third instar larvae failed to become adult when irradiated with 75, 100 and 150 Gy of gamma-ray. The impacts were increased with the increment of dose. Furthermore, impact of gamma-ray irradiation was greater on eggs compared to the third instar of larvae. The minimum dose of irradiation to prevent adults emerge was 118 Gy.